Cell-based therapy facilitates venous thrombus resolution - Santo, Stefano Di; Tepper, Oren M.; Ballmoos, Moritz Wyler von; Diehm, Nicolas; Völzmann, Jan; Baumgartner, Iris; Kalka, Christoph (Thrombosis and Haemostasis, 2009)
Endothelial progenitor cells (EPC) are involved in many healing processes in cardiovascular diseases and can be found in spontaneously resolving venous thrombi. The purpose of the present study was to investigate whether the therapeutic administration of EPC might enhance the resolution of venous thrombi. For this purpose, venous thrombosis was induced in the infrarenal inferior vena cava (IVC) in 28 athymic nude rats. Culture expanded EPC derived from human peripheral blood mononuclear cells were injected intravenously two and four days after thrombus induction. Recanalisation of the IVC and thrombus organisation were assessed by laser Doppler measurements of the blood flow and immunohistochemical detection of endothelialised luminal structures in the thrombus. EPC transplantation resulted in significantly enhanced thrombus neovascularisation (capillary density: 186.6 ± 26.7/HPF vs. 78 ± 12.3/HPF, p<0.01; area covered by capillaries: 8.9 ± 1.7 µm2 vs. 2.5 ± 1.3 µm2, p<0.01) and was accompanied by a substantial increase in intrathrombus blood flow (perfusion ratio: 0.7 ± 0.07 vs. 0.3 ± 0.08, p<0.02). These results were paralleled by augmented macrophage recruitment into resolving thrombi in the animals treated with EPC (39.4 ± 4.7/HPF vs. 11.6 ± 1.9/HPF, p<0.01). Our data suggest that EPC transplantation might be of clinical value to facilitate venous thrombus resolution in cases where current therapeutic options have limited success.
Keywords: Venous thrombosis; cell therapy; neovascularisation; endothelial progenitor cells; macrophages